Design versus artesanato: identidades e contrastes - Eguchi, Haroldo Coltri [UNESP]; Pinheiro, Olimpio José [UNESP] (My University, 2011)
There are at least three different visions about origins of design; the most diffused is the idea that design begins with the Industrial Revolution. Some see the design as heir of a special kind of crafts at Revolution’s eve, because it already have a former project and work division. Less diffused is the idea that there aren’t much significant differences between design and crafts, giving to design some millenniums of history. But, being the designer heir of this millenary tradition isn’t time to reconciliate it again with crafts? Shouldn’t we return to defend the rescue of concepts of project before the modernism?

Percebem-se pelo menos três visões distintas sobre a origem do design, sendo mais difundida a que situa seu inicio com a Revolução Industrial. Há quem veja o design como herdeiro de um artesanato às vésperas dessa Revolução que já contava com projeto e divisão do trabalho incipientes. Menos difundida é a idéia de que não há diferença tão significativa entre design e artesanato e, portanto, contaria com milênios de história. Supondo o designer herdeiro desta tradição milenar, não seria hora de voltar a reconciliá-lo com o artesanato? Não caberia voltar a defender o resgate de conceitos de projeto anteriores ao modernismo?
Design versus crafts: identities and contrasts
Keywords: Design and aesthetics; Design and culture; Design, art and technology; Design e estética; Design e cultura; Design, arte e tecnologia